Strategies for Teaching Language to Students with Special Needs - Nuryanti, Titik; Lim, Sofia; Tan, Ethan; Purnama, Yulian (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Teaching language to students with special needs presents unique challenges, requiring tailored strategies to address diverse learning abilities and disabilities. Despite the growing emphasis on inclusive education, there is limited research on effective language teaching methods for this population. This study explores strategies for teaching language to students with special needs, focusing on their impact on language acquisition and engagement. The research aims to identify and evaluate effective strategies for teaching language to students with special needs, focusing on their impact on language proficiency, engagement, and inclusivity. It seeks to provide practical recommendations for educators to create supportive and effective learning environments. A mixed-methods approach was employed, involving 50 students with special needs and their teachers. Data were collected through classroom observations, teacher interviews, and pre- and post-tests to measure language proficiency. Qualitative data were analyzed using thematic analysis, while quantitative data were analyzed using statistical software. The findings revealed that multisensory approaches, visual aids, and individualized instruction significantly improved language proficiency and engagement among students with special needs. Teachers reported that these strategies enhanced students' confidence and participation. However, challenges such as resource limitations and lack of training were also identified. Tailored strategies, such as multisensory approaches and individualized instruction, are effective in teaching language to students with special needs. Educators should prioritize inclusive practices and professional development to address challenges and enhance language learning outcomes.